Detection of blood protozoans in the urban rat populations of Peninsular Malaysia using quantitative buffy coat and giemsa-stained thin film techniques / Siti Norliyanti Alias - Siti Norliyanti , Alias (2017)
A total of 762 urban rats were trapped from four urban cities in Peninsular Malaysia namely Kuala Lumpur, Penang, Pahang and Malacca comprising of six urban rat species: Rattus rattus diardii (n=410), Rattus norvegicus (n=302), Rattus exulans (n=33), Rattus tiomanicus (n=8), Rattus argentiventer (n=7) and Rattus annandalei (n=2). It shows that Rattus rattus diardii was the highest amount to be caught which made up 53.8% of the total rats caught. The second highest to be trapped is Rattus norvegicus, making up 39.6% of the total rats caught. Followed by Rattus exulans (4.3%), Rattus tiomanicus (1.1%), Rattus argentiventer and Rattus annandalei with 0.9% and 0.3% respectively. Females were slightly higher at 52.8% and males at 47.2%. Adults captured were more with 502 rats (65.9%) compared to 152 sub adult rats (20.0%) and 108 juvenile rats (14.2%). Three hundred and thirty one rats were captured during dry season compared to 431 rats during wet season. Examination blood of rat from four localities of Peninsular Malaysia; Kuala Lumpur, Malacca, Pahang and Penang using Giemsa-stained Thin Film (GTF) technique and Quantitative Buffy Coat (QBC) technique resulted in identification of two blood protozoans (Trypanosoma sp. and Plasmodium sp.). Using Giemsa-stained Thin Film (GTF), a total of 456 rats (59.8%) were infected with at least one blood protozoan species from two species discovered namely; Trypanosoma sp. and Plasmodium sp. with prevalence of Plasmodium sp. (72.4%) higher compared to Trypanosoma sp. (42.1%). Only 14.5% (n =66) were found infected with both species. Rattus rattus diardii showed the highest prevalence of infection (62.2%), with 75.7% rats infected with Plasmodium sp., 38.8% infected with Trypanosoma sp. and 14.5% infected with both species. Using Quantitative Buffy Coat (QBC) technique, a total of 202 rats (46.8%) were infected with at least one blood protozoan species from two species discovered namely; Trypanosoma sp. and Plasmodium sp. with prevalence of Plasmodium sp. (61.4%) higher compared to Typanosoma sp. (44.6%). Only 5.9% (n =12) were found infected with both species. Rattus norvegicus showed the highest prevalence of infection (46.6%), with 63.1% rats infected with Plasmodium sp., 44.3% infected with Trypanosoma sp. and 7.4% infected with both species. In this study also have the comparison between the quantitative buffy coat (QBC) technique and conventional Giemsa thin blood smear. A total of 432 blood samples from four rat species (Rattus norvegicus, Rattus rattus diardii, Rattus exulans and Rattus argentiventer) were screened using both techniques and successfully detected two blood protozoan species (Trypanosoma sp. and Plasmodium sp.) with Trypanosoma sp. predominantly infecting the population. Results showed that Giemsa-stained thin film (GTF) was the better detection method on blood parasitemia (46.7%) compared to Quantitative Buffy Coat (QBC) (38.9%) with overall detection technique sensitivity and specificity at 83.2% and 74.8% respectively. The sensitivity in detection of Trypanosoma sp. was 84.4% with value slightly lower for Plasmodium sp. infections at 76.6%. Statistical analysis proved that GTF technique was significantly more sensitive in the detection of blood protozoan infections in the rodent population compared to QBC (p<0.05).